Cosmological Symmetry Breaking and Generation of Electromagnetic Field - Nagasawa, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
Cosmological phase transitions accompanied by some kind of symmetry breaking would cause the creation of topological defects and the resulting production of primordial magnetic field. Moreover, such a procedure inevitably affects the cosmic background radiation and it may be observed today. Motivated by the existence of stabilized embedded defects in the standard model of elementary interactions, we discuss their application to the cosmological electromagnetic field generation.